2017
DOI: 10.1002/mds.27107
|View full text |Cite
|
Sign up to set email alerts
|

Altered behavioral responses to gamma‐aminobutyric acid pharmacological agents in a mouse model of Huntington's disease

Abstract: The dysregulated GABAergic responses and altered expression levels of GABA receptors and potassium-chloride cotransporter-2 in Huntington's disease mice appear to be authentic and may contribute to the clinical manifestations of Huntington's disease patients. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…Recent proteomic and bioinformatic data linked (m)Htt and KCC2 ( 25 , 26 ), and in the present study, we provide the biochemical validation of this protein interaction. We found that KCC2 interacts with both Htt and mHtt and KCC2 protein expression is decreased in the hippocampus of two predominant mouse models of HD (R6/2 and YAC128), consistent with a recent report of decreased KCC2 protein expression in the cortex and striatum of R6/2 mice ( 49 ). While a decrease in Slc12A5 mRNA accounts for some of the reduction in KCC2 protein expression, there is still KCC2 protein present in hippocampal neurons of HD mouse models, and thus additional mechanisms likely also regulate KCC2 protein expression.…”
Section: Discussionsupporting
confidence: 91%
“…Recent proteomic and bioinformatic data linked (m)Htt and KCC2 ( 25 , 26 ), and in the present study, we provide the biochemical validation of this protein interaction. We found that KCC2 interacts with both Htt and mHtt and KCC2 protein expression is decreased in the hippocampus of two predominant mouse models of HD (R6/2 and YAC128), consistent with a recent report of decreased KCC2 protein expression in the cortex and striatum of R6/2 mice ( 49 ). While a decrease in Slc12A5 mRNA accounts for some of the reduction in KCC2 protein expression, there is still KCC2 protein present in hippocampal neurons of HD mouse models, and thus additional mechanisms likely also regulate KCC2 protein expression.…”
Section: Discussionsupporting
confidence: 91%
“…Decreased expression of KCC2 has been previously reported when increased NKCC1 was observed and may enable GABA to become excitatory . Likewise, our group and Dargaei et al reported reduced KCC2 expression in the cortices, striata, and hippocampi of multiple HD mouse models. Consistently, we and Dargaei et al reported that the stronger depolarization of E GABA was mainly because of the increased expression of NKCC1 in R6/2 mice rather than the reduced expression of KCC2, because acute application of an NKCC1 inhibitor, bumetanide, restored normal E GABA values.…”
Section: Discussionsupporting
confidence: 78%
“…RNA was isolated from mouse brains and human postmortem tissue and converted to cDNA using methods previously described . mRNA level was determined by quantitative PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the altered expression of GABA A Rs containing α1‐3 subunits essentially present in the postsynaptic domain, the expression of extrasynaptically localized α5‐ and δ‐containing GABA A Rs is also altered in human HD carriers and animal models . These extrasynaptic receptors are key factors in the control of local networks and are potential therapeutic targets for synthetic compounds or endogenous neuroactive steroids .…”
Section: Potential Therapeutic Avenuesmentioning
confidence: 99%
“…Besides the altered expression of GABA A Rs containing α1-3 subunits essentially present in the postsynaptic domain, the expression of extrasynaptically localized α5-and δ-containing GABA A Rs is also altered in human HD carriers and animal models. 69,94,95,129 These extrasynaptic receptors are key factors in the control of local networks 35 and are potential therapeutic targets for synthetic compounds or endogenous neuroactive steroids. 34,[130][131][132] On the basis of an increased expression of α5 in the striatum of R6/1 mice, 69 it would be relevant to test whether an α5-specific antagonist could slow disease progression or symptoms in HD, as is the case in mouse models of Down syndrome.…”
Section: P Otential Ther Apeuti C Aven Ue Smentioning
confidence: 99%